Surgical correction of residual deformities after ponseti treatment of club feet in walking children - Mohamed Awwad Abdeltawab; Amr Arafa; Mohamed Abdelmonem Elsobky; Mohamed Hegazi (Cairo : Mohamed Awwad Abdeltawab, 2018)
Clubfoot (congenital talipes equinovarus) is one of the most common birth deformities involving the musculoskeletal system. It consists of four components: fore-foot cavus, fore-foot adduction, hind-foot varus, and hind-foot equinus. There is almost a universal agreement on the good result of non-operative treatment of clubfoot deformity represented in Ponseti casting technique. Clubfoot relapses or residual deformities after ponseti treatment continue to be a problem in caring for the children with club feet especially in walking age. In our study 35 feet in 29 children with residual deformities of clubfoot previously treated by Ponseti serial casting underwent different selective surgical procedures (soft tissue and bony procedures) according to the residual deformity present, the age of the patient, and the rigidity of the deformity. Comparison between pre and post-operative values was done using paired t test. P values less than 0.05 was considered statistically significant. We used the Pirani score to classify the postoperative results to 4 categories; excellent result (Pirani score 0): 17 cases (48%), good results (Pirani score 0.5 --1): 10 cases (29%), fair result (Pirani score 1.5- 2): 7 cases (20%), poor result (Pirani score 2.5- 6): 1 case (3%). Finally, we concluded that combined ponseti technique and selective surgery is effective for management of the residual deformities of club foot in walking children
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Orthopedic Surgery
Issued also as CD
Keywords: Club foot; Ponseti treatment; Residual deformity